The Importance of Stunting Prevention in Children in Simpang Tiga Village, Sawit Seberbang, Langkat District - Faried, Annisa Ilmi; Sembiring, Rahmad; Sari, Maya Macia (Universitas Negeri Medan, 2023)
In Indonesia, the National Strategy (Stranas) for the Acceleration of Stunting Child Prevention for the 2018-2024 period is a guide document for the implementation framework for stunting reduction. Following up on this, the government issued Presidential Regulation (Perpres) Number 72 of 2021 concerning the Acceleration of Stunting Reduction with the intention of strengthening the intervention and institutional framework in the process of implementing the acceleration of stunting reduction. A condition known as stunting occurs when a child's height is much lower than expected for their age. In addition to being physically shorter than classmates, children with stunted development often experience cognitive impairment and weakened immunity. If a child suffers from stunting, the effects are generally never reversible. A solution is in sight, despite the fact that there is still a significant threat to the safety of millions of young people. A number of elements, including the consumption of food throughout the first thousand days of a person's life (HPK). To achieve the target of 14 percent by 2024 as stipulated in the 2020-2024 RPJMN, future stunting eradication measures must be strengthened and accelerated. It is hoped that all parties involved will care and participate in efforts to prevent stunting in children. It has to do with community service. Previous research on elements related to stunting in children and toddlers was carried out in support of this service. The findings are that maternal characteristics, such as mother's height and education level, are related to the occurrence of stunting in children and toddlers Girls who are now teenagers will become mothers in the next generation. The importance of getting education for adolescents, especially in raising awareness about various methods to reduce stunting can break the chain that leads to the prevalence of stunting in children and toddlers.